Chuyện mười phụ nữ huyền thoại Việt Nam - Thu Hằng (Hà Nội : Văn học, 2004)
Hai Bà Trưng; Bà Triệu; Ỷ Lan; Bùi Thị Xuân; Đoàn Thị Điểm; Hồ Xuân Hương; Bà Huyện Thanh Quan; Lê Ngọc Hân; Võ Thị Sáu; Nguyễn Thị Định.
Keywords: Việt Nam; Phụ nữ -- Việt Nam